2021
DOI: 10.3390/met11071036
|View full text |Cite
|
Sign up to set email alerts
|

Heat Treatment Evaluation for the Camshafts Production of ADI Low Alloyed with Vanadium

Abstract: Ductile iron camshafts low alloyed with 0.2 and 0.3 wt % vanadium were produced by one of the largest manufacturers of the ductile iron camshafts in México “ARBOMEX S.A de C.V” by a phenolic urethane no-bake sand mold casting method. During functioning, camshafts are subject to bending and torsional stresses, and the lobe surfaces are highly loaded. Thus, high toughness and wear resistance are essential for this component. In this work, two austempering ductile iron heat treatments were evaluated to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
2
0
1
Order By: Relevance
“…In other words, the higher the temperature, the lower the hardness and vice versa, and the longer the treatment time, the lower the hardness and vice versa. This behavior has also been documented by other authors [60][61][62], and these materials exhibited excellent wear resistance and tensile strength properties for their possible application as high-performance components.…”
Section: Quantification Of Error In Regressionssupporting
confidence: 79%
“…In other words, the higher the temperature, the lower the hardness and vice versa, and the longer the treatment time, the lower the hardness and vice versa. This behavior has also been documented by other authors [60][61][62], and these materials exhibited excellent wear resistance and tensile strength properties for their possible application as high-performance components.…”
Section: Quantification Of Error In Regressionssupporting
confidence: 79%
“…This result is consistent with previous studies , which also found that V is the most influential element on the mechanical properties of low alloy steel. In addition, studies by Goritskii et al (2016) and García et al (2021) also showed that higher V concentrations can increase the tensile strength and hardness of low alloy steel. Higher concentrations of Ni (Nickel) and Mn (Manganese) can also increase the tensile Leni D, Sumiati R, Adriansyah, Angelia N, Nofriyanti E, 2023, The Influence of Heatmap Correlation-based Feature Selection on Predictive Modeling of Low Alloy Steel Mechanical Properties Using Artificial Neural Network (ANN) Algorithm, Journal of Energy, Material, and Instrumentation Technology Vol.…”
Section: Feature Selectionmentioning
confidence: 97%
“…El proceso se realizó para las temperaturas de austemperizado de 265 y 305 °C, de acuerdo con el ciclo térmico mostrado en la Figura 2. Los parámetros de temperatura de austemperizado y mezcla de sales han sido previamente reportados para composiciones similares en ADIs aleados con vanadio (Colin et al, 2021). En adición, la mezcla de sales fue obtenida en base al diagrama KNO3 y NaNO3, mientras que las temperaturas de 265 y 305 °C para obtener ausferrita fina con diferentes cantidades de austenita de alto carbono.…”
Section: Tratamiento Térmico De Austemperizadounclassified